A Simple Formula for the Expected Rate of Return of an Option over a Finite Holding Period - RUBINSTEIN, MARK (Journal of Finance, 1984)
ABSTRACT Under conditions consistent with the Black‐Scholes formula, a simple formula is developed for the expected rate of return of an option over a finite holding period possibly less than the time to expiration of the option. Under these conditions, surprisingly, the expected future value of a European option, even prior to expiration , is shown equal to the current Black‐Scholes value of the option, except that the expected future value of the stock at the end of the holding period replaces the current stock price in the Black‐Scholes formula and the future value of a riskless invesment of the striking price replaces the striking price. An extension of this result is used to approximate moments of the distribution of returns from an option portfolio.